Halsey & Co. : or, The Young Bankers and Speculators - Shackleford, H. K. (Harvey King), 1841-1906 (Salt Lake City, UT : Project Gutenberg, 2007)
"Halsey & Co.; or, The Young Bankers and Speculators" by H. K. Shackleford is a novel likely written in the late 19th century. The story follows the adventures of Fred Halsey, a resourceful young newsboy who takes on criminals and finds himself embroiled in the world of finance and stock trading. After foiling an attempted bank fraud, Fred earns a reward and decides to dive into the world of banking and speculation with his close friend, Bob Newcombe. The opening of the novel introduces Fred as he alerts a banker about two men plotting to present a forged check. His bravery leads to the capture of the forger and earns him both praise and a reward, providing him a newfound sense of wealth and purpose. As Fred revels in his good fortune, he dreams of starting his own bank. The narrative not only highlights his quick thinking and determination but also sets up his subsequent ventures into the stock market, where he navigates challenges, makes new friends, and seeks to build a successful future against the backdrop of Wall Street's high-stakes environment. (This is an automatically generated summary.)
Release date is 2007-06-29
Produced by Richard Halsey
Keywords: Boys -- Juvenile fiction; Wall Street (New York, N.Y.) -- Juvenile fiction